If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -9 = 6x + 4 Reorder the terms: -9 + 12x = 6x + 4 Reorder the terms: -9 + 12x = 4 + 6x Solving -9 + 12x = 4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -9 + 12x + -6x = 4 + 6x + -6x Combine like terms: 12x + -6x = 6x -9 + 6x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 + 6x = 4 + 0 -9 + 6x = 4 Add '9' to each side of the equation. -9 + 9 + 6x = 4 + 9 Combine like terms: -9 + 9 = 0 0 + 6x = 4 + 9 6x = 4 + 9 Combine like terms: 4 + 9 = 13 6x = 13 Divide each side by '6'. x = 2.166666667 Simplifying x = 2.166666667
| 0=7m | | 0.9x+0.2x-6=5 | | (x-1)5=(x-2)3 | | 2x^2-27x-80=0 | | 88=125-(-x) | | 9y=-270 | | 1.8w+2.8=2.5w+2.1 | | 42x=x+2 | | X-(1/3x)=800 | | 2w-5=3(1-2w) | | X+(2x-1)=23 | | 24=3/8x | | 180=-6x | | on(2-3x)=8 | | -x-4=15 | | (x^2-2x+1)(x^2+5x+6)=0 | | -6x+5=-4x-19 | | 5x^3=120 | | .57x=18 | | (-5x^2)-(-9x^2)= | | 3x+3x+-1=4x+9 | | -4(m+6)=.8 | | p/9-5=2 | | 4(x+7)+3x=12+4x-5 | | (2y+7)(8y^2-6y+1)=0 | | 4n+9=2n+13 | | 142=5x-6(-4x+15) | | 3t+12=2t+14 | | -x^2+4y^2-20x+8y-92=0 | | 4q=x+12 | | x+10+3(x+6)=180 | | 4x-(-12x+24y)y=4 |